Approach for the Handling of Non-Hazardous Usable Residues Using an Ecological Station - Malaver Flor, Cesar Rodrigo; Trullo Guerrero, Ricardo José; Caicedo Muñoz, Julian A.; Mosquera Bolaños, Julián Andrés (Ingeniería Solidaria, 2016)
Introduction: This article is the result of the research project “Ecological Station based on renewable energies” currently developed by the Research Group on Technology and environment (gita) of the Corporación Universitaria Autónoma del Cauca and funded by the Human Talent Education Network Project for Social and Productive Innovation in the department of Cauca (InnovAcción Cauca), for a period of one year (September 2015 to 2016, the same month). Methodology: A review of the literature regarding the management of usable non-hazardous waste RnPA) is made, and includes technological trends and Management strategies. Additionally, a comparison is made based on the objectives of environmental education and major gaps and voids present when handling RnPA. Results: the architecture of an eco-friendly station (eco-station) as a pedagogical strategy, which integrates different forms of learning into the management RnPA during the collection stage. Conclusions: material detection systems, user interaction, selection of waste and renewable energy supply within the eco-station streamline the learning process in the management and collection of RnPA at the source.